18F-Florbetapir and 18F-FDG PET/CT in Systemic Immunoglobulin Light Chain Amyloidosis Involving the Peripheral Nerves. (February 2016) - Broski, Stephen M.; Spinner, Robert J.; Howe, Benjamin M.; Dispenzieri, Angela; Johnson, Geoffrey B.
Abstract : Abstract: We present a case of both 18 F-FDG and 18 F-florbetapir uptake in a biopsy-confirmed immunoglobulin light chain (AL) amyloidosis involving the peripheral nerves. AL amyloidosis is the most common cause of acquired amyloid polyneuropathy, manifesting with both sensorimotor and autonomic neuronal dysfunction. Given the overlapping MRI and FDG PET/CT appearances of several different causes of peripheral neuropathy, 18 F-florbetapir PET/CT provides another potential tool in the imaging algorithm of these patients and may guide targeted fascicular biopsy for pathologic confirmation.